Two new species of Borreria (Rubiaceae) from Brazil, with new distributional records for Pará State and a key to species with transversally sulcate seeds - Cabral, Elsa Leonor (2012)
Fil: Cabral, Elsa Leonor. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.